2015
DOI: 10.1038/ncomms9250
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic site inhibition of insulin-degrading enzyme by a small molecule induces glucose intolerance in mice

Abstract: Insulin degrading enzyme (IDE) is a protease which cleaves insulin and other bioactive peptides such as amyloid-β. Knock-out and genetic studies have linked IDE to Alzheimer's disease and type-2 diabetes. As the major insulin degrading protease, IDE is a candidate drug target in diabetes. Here we use kinetic Target-Guided Synthesis to design the first catalytic site inhibitor of IDE suitable for in vivo studies (BDM44768). Crystallographic and SAXS analyses shows that it locks IDE in a closed conformation. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 45 publications
2
107
1
1
Order By: Relevance
“…In diabetic subjects, IDE levels in the cytosol are reduced and consequently more and more IDE synthesis is needed for complete insulin degradation. Support for this mechanism of insulin resistance is indicated in the fact that inhibition of IDE with BDM44768 resulted in impaired glucose tolerance [85]. However, others have reported that IDE deficiency actually improved glucose tolerance [108] and based on this, some researchers are now proposing the use of IDE inhibitors as an anti-diabetes agent [86].…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic subjects, IDE levels in the cytosol are reduced and consequently more and more IDE synthesis is needed for complete insulin degradation. Support for this mechanism of insulin resistance is indicated in the fact that inhibition of IDE with BDM44768 resulted in impaired glucose tolerance [85]. However, others have reported that IDE deficiency actually improved glucose tolerance [108] and based on this, some researchers are now proposing the use of IDE inhibitors as an anti-diabetes agent [86].…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
“…However, others have reported that IDE deficiency actually improved glucose tolerance [108] and based on this, some researchers are now proposing the use of IDE inhibitors as an anti-diabetes agent [86]. Deprez-Poulain et al [85] reported that IDE is involved in pathways that modulate short-term glucose homeostasis, but casts doubt on the general usefulness in the inhibition of IDE to treat diabetes. The effect of IDE levels on blood glucose control is therefore controversial.…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
“…Substantial in vitro and in cyto evidence supports the role of IDE in the clearance of insulin [1]. Furthermore, IDE null mutants, gene knockout, and pharmacological inhibition in rodents all result in elevated blood insulin levels (hyperinsulinemia) [5, 25, 26, 28, 29]. …”
Section: Ide Substrates and Functionsmentioning
confidence: 99%
“…With the advance in the structural analysis of IDE, at least five IDE inhibitors, including Ii1, BDM41367, 6bk, BDM44768, and NTE1, have been characterized structurally to elucidate how they bind IDE to inhibit its activity [5, 29, 6770] (Figure 3). IDE inhibitor 1 (Ii1), the first reported high affinity IDE inhibitor (~2 nM), is a peptidomimetic hydroxamate that binds the catalytic site of IDE [67].…”
Section: Ide Inhibitors: Therapeutic Potential and Challengesmentioning
confidence: 99%
“…Evidence supporting a role for IDE in degrading insulin and Aβ in vivo includes associations of IDE gene variants with type 2 diabetes (1, 2) and Alzheimer's disease (3,4), decreased clearance of the two peptides in IDE-deficient mice (5,6), and antidiabetic activity produced by IDE inhibitors (7,8), although some reports have questioned its role in insulin degradation (9,10). In addition, IDE has been reported to have noncatalytic functions, such as acting as a receptor for varicella-zoster virus (11) and serving as a heat shock protein in stressed cells (12).…”
mentioning
confidence: 99%